2021
DOI: 10.1021/jacs.1c02772
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of P-Stereogenic Secondary Phosphine-Boranes by an Unsymmetric Bisphosphine Pincer-Nickel Complex

Abstract: The first highly enantioselective catalytic synthesis of P-stereogenic secondary phosphine-boranes was realized by the asymmetric addition of primary phosphine to electron-deficient alkenes with a newly developed unsymmetric bisphosphine (PCP′) pincer-nickel complex. Various P-stereogenic secondary phosphine-boranes were obtained in 57−92% yields with up to 99% ee and >20:1 dr. The follow-up alkylation upon P−C bond formation with alkyl halides provided a practical way to access P-chiral compounds with diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(42 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…A chiral pincer bisphosphane Ni complex was used in the first highly enantioselective catalytic synthesis of P-stereogenic secondary phosphane-boranes by the asymmetric hydrophosphination of electron-deficient alkenes with phenylphosphane. Various P-stereogenic secondary phosphane-boranes were obtained in 57-92% yields with up to 99% ee [54]. The Togni group developed the asymmetric hydrophosphination of vinyl nitriles catalyzed by a dicationic Ni-based complex yielding the desired phosphane product with 32-94% ee [55,56] (Figure 14).…”
Section: Hydrophosphination Reactions Of Alkenes and Alkynesmentioning
confidence: 99%
“…A chiral pincer bisphosphane Ni complex was used in the first highly enantioselective catalytic synthesis of P-stereogenic secondary phosphane-boranes by the asymmetric hydrophosphination of electron-deficient alkenes with phenylphosphane. Various P-stereogenic secondary phosphane-boranes were obtained in 57-92% yields with up to 99% ee [54]. The Togni group developed the asymmetric hydrophosphination of vinyl nitriles catalyzed by a dicationic Ni-based complex yielding the desired phosphane product with 32-94% ee [55,56] (Figure 14).…”
Section: Hydrophosphination Reactions Of Alkenes and Alkynesmentioning
confidence: 99%
“…Very recently, Wang et al demonstrated the synthesis of unsymmetrical PCP′ pincer nickel complexes bearing a phosphine-phosphinite ligand with a stereogenic carbon center [ 152 ]. The corresponding enantiopure nickel complexes 55a and 55b were obtained via a convenient one-pot three-step reaction ( Scheme 31 ).…”
Section: Other Types Of Complexesmentioning
confidence: 99%
“…A wide range of phosphine chemistry has been developed, with metal catalyzed hydrophosphination being one of the most economic avenues for P-C bond formation. Though significant progress has occurred [1,7,[15][16][17][18][19][20][21][22][23][24], challenges remain for this transformation, with catalyst and substrate scope being two key avenues for improvement [1,15,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%